Effects of Parental Attitudes in Childhood on Depressive Symptoms Through Trait Anxiety and Negative Life Events in Adult Volunteers - Hayashida T; Kikkawa M; Masuya J; Ono M; Ito S; Nibuya R; Takashio O; Tamada Y; Hashimoto N; Inoue T (Neuropsychiatric Disease and Treatment)
Taito Hayashida,1,* Masayuki Kikkawa,1,* Jiro Masuya,1 Miki Ono,1 Shunichiro Ito,1 Rintaro Nibuya,1 Osamu Takashio,2 Yu Tamada,2 Naoki Hashimoto,3 Takeshi Inoue1,4 1Department of Psychiatry, Tokyo Medical University, Tokyo, Japan; 2Department of Psychiatry, Tokyo Medical University Hachioji Medical Center, Tokyo, Japan; 3Department of Psychiatry, Hokkaido University Graduate School of Medicine, Hokkaido, Japan; 4Department of Psychiatry, Sapporo Hanazono Hospital, Hokkaido, Japan*These authors contributed equally to this workCorrespondence: Takeshi Inoue, Department of Psychiatry, Tokyo Medical University, 6-7-1 Nishi-shinjuku, Shinjuku-ku, Tokyo, 160-0023, Japan, Tel +81-3-3342-6111, Email tinoue@tokyo-med.ac.jpBackground: The mechanism underlying how parental attitudes in childhood, trait anxiety (TA), and adult life events cause depression remains unclear. In this study, we investigated the associations among parental attitudes in childhood, TA, adult life events, and depressive symptoms to assess the mechanism of the development of depressive symptoms.Participants and Methods: This study was conducted between January and August 2014. A total of 404 Japanese adult volunteers completed questionnaires, including Parental Bonding Instrument, State-Trait Anxiety Inventory Form Y, Life Experiences Survey, and Patient Health Questionnaire‐9, to assess the parental attitudes of care and overprotection experienced in childhood, TA, life events, and depressive symptoms, respectively. The associations among these variables were analyzed by structural equation modeling.Results: Parental attitude did not affect depressive symptoms directly, but affected TA directly. The influence of “care” on TA was negative, but that of “overprotection” on TA was positive. TA had a positive influence on negative life events (NLEs) and depressive symptoms in adulthood. Although NLEs in adulthood had a positive influence on depressive symptoms, positive life events in adulthood did not have any effect. Regarding indirect effects, parental attitude influenced NLEs and depressive symptoms through TA. TA worsened depressive symptoms through NLEs in adulthood. Regarding the parental attitude subscale of “care”, this decreased depressive symptoms through TA and NLEs in adulthood. Care and overprotection showed opposite effects. The model fit was good or acceptable (Comparative Fit Index > 0.97 and Root Mean Square Error of Approximation < 0.08).Conclusion: This study suggested that parental attitudes in childhood influence adult depressive symptoms through TA and NLEs. Improving the quality of child care may decrease TA, reduce NLEs in adulthood, and reduce depressive symptoms indirectly. Guidance for parents and interventions to reduce TA may be useful for the prevention of depression in adulthood.Keywords: parental attitudes, trait anxiety, negative life events, depressive symptoms, structural equation modeling